Effects of Larval Starvation Stress on the Life History and Adult Fitness of Fall Webworm, Hyphantria Cunea - Yuan Zhang; Lin Zhang; Junchao Zheng; Tongpu Li; Lvquan Zhao (Insects)
Insects often encounter starvation stress, especially during invasion spread or population outbreaks. The fall webworm, Hyphantria cunea (Drury) (Lepidoptera: Arctiidae), is an important invasive pest in China, and the starvation resistance of its larvae determines population spread and resulting outbreak threat. In this study, we investigated the starvation resistance of H. cunea larvae and the effects of starvation stress on their life history and adult fitness. Larval starvation resistance increased along with the instar stage, and the second-day sixth instar molt was critical for starvation resistance. The response to starvation stress was reflected in multiple biological indicators observed in H. cunea. Complete food deprivation reduced the pupation survival rate of sixth instar larvae, prolonged their developmental duration, reduced pupal and adult body mass, shortened adult forewing length and lifespan, and reduced female egg production. The sixth instar larvae showed a certain ability to recover after refeeding. However, negative impacts of the starvation period on larval life history traits, such as pupation survival rate, pupal and adult body mass, adult longevity, and fecundity, were still observed even after refeeding, and the effects of refeeding were affected by larval starvation duration and refeeding mode. These results suggested that H. cunea larvae were highly resistant to starvation, that starvation stress negatively affected their larval life history and adult fitness, and that the pattern of the effects of post-starvation refeeding on larval and adult fitness was related to the duration of starvation and the refeeding mode. The results of this study offer important insights into understanding the physiological response mechanisms of invasive insects under starvation stress.